A Systematic Approach to Enhancing Occupational Safety and Health Management using Job Safety Analysis - Anthara, I Made Aryantha; Robecca, Julian; Gumilar, Arcellia Citra Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Occupational Safety and Health  is an important aspect in preventing accidents and protecting the health of workers, especially in high-risk work environments. Every production activity has the potential for hazards that can cause injury if not controlled properly. This research was carried out at PT Kereta Api Indonesia (Persero) Balai Yasa Kiaracondong Bridge unit with the object of the Pen Puller manufacturing process. The production stages include material removal, cutting, perforation, welding, smoothing, painting, and packaging that contain potential physical, mechanical, chemical, and ergonomic hazards. The method used is Job Safety Analysis (JSA) through the identification of work steps, determination of potential hazards, and the preparation of risk control measures.. The results of the study show that JSA is effective in helping to identify hazards and improve the implementation of K3. Companies are advised to increase supervision of the use of personal protective equipment and conduct regular JSA evaluations